THE GEOGRAPHY OF SERBIA - Pecelj, Milovan R. (Journal of the Geographical Institute “Jovan Cvijić” SASA, 2021)
The manuscript represents a review of the monograph publication entitled The Geography of Serbia, published by the Geographical Institute ''Jovan Cvijić'' SASA in Belgrade. The aim of the review is to present this significant book to the scientific community, which gathered fifty-six, mainly young researchers who courageously accepted to write the study of special national importance, and include a vast geographical material from physical geography, human geography and related disciplines into a unique whole.